A coupled computational framework for bone fracture healing and long‐term remodelling: Investigating the role of internal fixation on bone fractures. (11th May 2022) - Quinn, Conall; Kopp, Alexander; Vaughan, Ted J.
Abstract: In this study, a coupled computational modelling framework for bone fracture repair is presented that enables predictions of both healing and remodelling phases of the fracture region and is used to investigate the role of an internal fixation plate on the long‐term healing performance of a fracture tibia under a range of different conditions. It was found that introduction of a titanium plate allowed the tibia to undergo successful healing at higher loading conditions and fracture gaps, compared with the non‐plated versions. While these plated cases showed faster rates of repair in the healing phase, their performance was substantially different once they entered the remodelling phase, with substantial regions of stress shielding predicted. This framework is one of the few implementations of both fracture healing and remodelling phases of bone repair and includes several innovative approaches to smoothing, time‐averaging and time incrementation in its implementation, thereby avoiding any unwanted abrupt changes between tissue phenotypes. This provides a better representation of tissue development in the fracture site when compared with fracture healing models alone and provides a suitable platform to investigate the long‐term performance of orthopaedic fixation devices. This would enable the more effective design of permanent fixation devices and optimisation of the spatial and temporal performance of bioabsorbable implants. Abstract : A coupled computational framework for bone fracture healing and long‐term remodelling: Investigating the role of internal fixation on bone fractures.